IMPLEMENTATION OF THE BEAUTIFUL MALANG PROGRAM THROUGH THE “MALANG MENYAPA” APPLICATION - Aminah, Laila Siti; Dja’far, Veri Hardinansyah; Arifin, Wahyu Eko (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
The objective of this study is to identify and analyze the Malang Menyapa application's implementation as the Beautiful Malang Program of the Malang City Culture and Tourism Office. The research method employed is descriptive research using a qualitative approach to ascertain the subject's description. The library research was used to collect data for this study. If the observations of field researchers on the implementation of smart city policies in the city of Malang are compared to a theory confirmed by Edward III, numerous variables must be considered, particularly communication, resources, disposition, and organizational structure. The Department of Culture and Tourism of the city of Malang developed an application, namely “Malang Menyapa”, in order to develop a beautiful Malang program in the city of Malang that is based on a smart city, particularly in the culture and tourism sector, to be implemented in the city of Malang. Hopefully, by the presence of this application will result in an increase in tourists, which will help to accelerate the inflation rate of regional economic growth.